Grèce, le prix d’un enfant/ Public Sénat, 7/3/2016. Greek surrogate motherhood from the French point of you: Critical enquiries and theoretical perspectives. - Μαροπούλου (Marina Maropoulou) Μαρίνα (Bioethica, 2017)
This paper reassesses surrogate motherhood as a legal category within the practice of bio-medicine, as well as a legal relation within the human family.The current study approaches the legal form of the received Greek legislation concerning gestational surrogate motherhood -the altruistic form of surrogate motherhood (non payment),through a multidimensional perspective. The shortcomings of the law regarding the legal understanding of surrogate mother’s contribution and role, the stereotypical views concerning gender roles both within the private and the public domains, as well as the exclusive focus on the protection of the reproductive rights and the parental status of the intended parents result in the inability to identify the surrogate mother within a legal protective frame as mother, working person, citizen. This fact produces and reproduces a vicious circle. Surrogate mothers are recruited from an always already invisible social group, the poor immigrant women. The absence of their legal protection and acknowledgment forces them to remain in this condition of invisibility and secures the continuity of this reproductive labour. The paper also readdresses the surrogate motherhood as a bio-ethic issue, from a critical, gender sensitive viewpoint. It raises the question if this practice transforms the persons who give life into mere, anonymous biological material; it raises questions regarding the extent to which this practice commodifies and appropriates women’s bodies. The paper finally addresses a demand for a more comprehensive reproductive justice and a more inclusive social protection for surrogate motherhood.